Genomic Diversity of the Ostreid Herpesvirus Type 1 Across Time and Location and Among Host Species - Morga, Benjamin; Jacquot, Maude; Pelletier, Camille; Chevignon, Germain; Dégremont, Lionel; Biétry, Antoine; Pepin, Jean-François; Heurtebise, Serge; Escoubas, Jean-Michel; Bean, Tim P.; Rosani, Umberto; Bai, Chang-Ming; et al. (Frontiers in Microbiology, 2021)
The mechanisms underlying virus emergence are rarely well understood, making the appearance of outbreaks largely unpredictable. This is particularly true for slowly evolving pathogens such as DNA viruses because they do not exhibit a sufficient amount of evolutionary change among genetic sequences sampled at different time points to make them suitable for analytical techniques derived from population genetic theory. However, current sequencing technologies have created unprecedented opportunities for studying microbial populations and previous distinctions between slow- and fast-evolving pathogens become blurred once evolution is assessed at a genome-wide scale. Here, we aim to assess the measurability of evolution on epidemiological time scales of the Ostreid herpesvirus 1 (OsHV-1), a double stranded DNA virus of which a new variant, OsHV-1μVar, emerged in France in 2008 , spreading to many European countries and causing dramatic economic and ecological damages. We performed phylogenetic analyses of heterochronous OsHV-1 genomes sampled worldwide. Results show sufficient temporal signal in the viral sequences to proceed with phylogenetic molecular clock analyses and they indicate that the present genetic diversity seen in OsHV-1 isolates has arisen within the past three decades. OsHV-1 samples from France and New Zealand did not cluster together suggesting a spatial structuration of the viral populations. The genome-wide study of simple and complex polymorphisms shows that specific genomic regions are deleted in several isolates or accumulate a high number of substitutions. These contrasting and non-random patterns of polymorphism suggest that some genomic regions are affected by strong selective pressures. Interestingly, we also found variants within all infected individuals. Altogether, these results provide baseline evidences that whole genome sequencing could be used to study population dynamic processes of OsHV-1, and more broadly herpesviruses.